Evaluation of the cardioprotective potential of extracellular vesicles – a systematic review and meta-analysis. Issue 1 (December 2018) - Wendt, Sebastian; Goetzenich, Andreas; Goettsch, Claudia; Stoppe, Christian; Bleilevens, Christian; Kraemer, Sandra; Benstoem, Carina
Abstract Cardiovascular diseases are the main cause of death worldwide, demanding new treatments and interventions. Recently, extracellular vesicles (EVs) came in focus as important carriers of protective molecules such as miRNAs and proteins which might contribute to e.g. improved cardiac function after myocardial infarction. EVs can be secreted from almost every cell type in the human body and can be transferred via the bloodstream in almost every compartment. To provide an all-encompassing overview of studies investigating these beneficial properties of EVs we performed a systematic review/meta-analysis of studies investigating the cardioprotective characteristics of EVs. Forty-three studies were investigated and catalogued according to the EV source. We provide an in-depth analysis of the purification method, size of the EVs, the conducted experiments to investigate the beneficial properties of EVs as well as the major effector molecule encapsulated in EVs mediating protection. This study provides evidence that EVs from different cell types and body fluids provide cardioprotection in differentin vivo andin vitro studies. A meta-analysis was performed to estimate the underlying effect size. In conclusion, we demonstrated that EVs from different sources might serve as a promising tool for treating cardiovascular diseases in the future.